Combined approach to strategic analysis of the financial condition of organizations - E. V. Berezhnaya; A. V. Savtsova; N. V. Zelensky (Вестник Северо-Кавказского федерального университета)
Introduction. The matrix approach is one of the common analytical tools in economic science. Its application is not very limited, and it serves as a supplement to a number of other analytical tools. In particular, matrices are built on the basis of quantitative indicators of various aspects of corporate activity: market share, revenue, sales growth rates, etc. The paper puts emphasis on modeling using a combination of matrices and financial ratios of the financial strategy and financial policy of the company.Goal. The paper develops a combined approach to the strategic analysis of the financial condition of organizations and their positioning using financial coefficients and matrices.Materials and methods. The information base of the study included statistical materials from the SPARK database, financial statements of companies manufacturing chemical products in two types of activities. The proposed approach was tested using open data for 2022-2023. The authors modified the revenue / profit matrix by A. Slywotsky and D. Morrison. The interpretation of the indicators used for the matrix axes was proposed. They were processed into relative values in order to level out the influence of volumetric values on the analysis results. The indicators that characterize companies along the profit axis were clarified. Criteria values for determining high and low levels of revenue and profit were proposed and tested, and the shortcomings and prospects for their application were analyzed. The work is based on the works of economists in the field of finance and risk management, strategic analysis, and presents the development of the earlier works made by the authors.Results and discussion. The authors tested the proposed combined approach to assessing the financial condition on the basis of a typical sample of chemical industry companies divided into two groups by the type of activity. Two types of average values were calculated in accordance with the general scientific concept of sustainability. Based on the approach used in the Bowman paradox, the distribution of companies in the industry was calculated depending on the level of their revenue and profit. At the end, using the example of several large companies, the problems and possibilities of assessing indicators within the framework of the matrix approach are shown.Conclusion. Based on the results of the study, the authors made conclusions about the problems in the selected area and proposed directions for further research. In particular, it is advisable to further clarify the criteria boundaries for assessing the financial indicators used in the matrix and improve the set of indicators for assessment and the interpretation of the matrix cells.